Susunan Tim Editorial - Admin psycho Idea (Psycho Idea, 2020)
Chief Editor :Imam Faisal Hamzah(Universitas Muhammadiyah Purwokerto, Indonesia) Managing Editor :Tri Naimah(Universitas Muhammadiyah Purwokerto, Indonesia) Associate Editor :Endah Kumala Dewi(Universitas Diponegoro, Indonesia)Fathul Lubabin Nuqul(Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia)Erita Yuliasesti Diah Sari(Universitas Ahmad Dahlan Yogyakarta, Indonesia)Herdian(Universitas Muhammadiyah Purwokerto, Indonesia;Studi Doktoral Nanjing Normal University, Tiongkok)Retno Dwiyanti(Universitas Muhammadiyah Purwokerto, Indonesia;Studi Doktoral Universiti Pendidikan Sultan Idris, Malaysia) Section Editor :Fatin Rohmah Wahidah(Univeritas Muhammadiyah Purwokerto, Indonesia)